Music as an emotion regulation strategy: An examination of genres of music and their roles in emotion regulation. (January 2019) - Cook, Terence; Roy, Ashlin R. K.; Welker, Keith M.
Research suggests that people frequently use music to regulate their emotions. However, little is known about what kinds of music may regulate affective states. To investigate this, we examined how the music preferences of 794 university students were associated with their use of music to regulate emotions. We found that preferences for pop, rap/hip-hop, soul/funk, and electronica/dance music were positively associated with using music to increase emotional arousal. Soul/funk music preferences were also positively associated with using music for up-regulating positive emotionality and down-regulating negative emotionality. More broadly, energetic and rhythmic music was positively associated with using all examined forms of musical emotion regulation, suggesting this dimension of music is especially useful in modulating emotions. These results highlight the potential use of music as a tool for emotion regulation. Future research can extend our findings by examining the efficacy of different types of music at modulating emotional states.